基于Pro/E和ADAMS的圆柱分度凸轮机构建模及仿真 - 王晓辉; 廉哲满 (Jixie chuandong)
By the spatial coordinate transformation theory and conjugate theory the mathematic model of cylindrical indexing cam mechanism is established,and then by the 3D modeling software Pro/E,its 3D solid model is built,and the simulation of cylindrical indexing cam mechanism is carried out.The simulation results show that,the input rotation speed of cam and the preload torque of disc have an obvious effect on the angular acceleration of the cylindrical indexing cam mechanism.